(untitled) (Asian Education Studies, 2016)
Self-efficacy has been persistently cited as a major component in understanding how frequently and successfully individuals use technology. Preservice teachers’ technology self-efficacy is a creditable indicator of graduates’ likelihood to use instructional technology throughout their careers; thus, it is imperative that new teachers graduate with a high sense of self-efficacy regarding their abilities to use technology as an effective teaching tool. The purpose of this study was to determine preservice teachers’ self-efficacy beliefs related to integrating technology into instruction. Elementary preservice teachers (n=28) from a single university completed a Likert-type survey using a forced choice scale with six points. Responses to the 5-item survey were converted to numerical data, and the research question was examined using descriptive statistics. Data indicated that almost all (93%) of the participants incorporated technology into the lessons they taught with the majority (68%) of participants reporting a high level of confidence in their ability to select and utilize technology in teaching. Further, 89% of the participants felt they could integrate technology across the curriculum with 80% indicating they were capable of determining the why, when, and how to do so most of the time.